2013
DOI: 10.1097/crd.0b013e31828af110
|View full text |Cite
|
Sign up to set email alerts
|

Medico-Legal Issues in Cardiology

Abstract: The aim of this article is to educate physicians about the current litigation climate in cardiology and cardiac surgery, with a focus on the most frequently litigated areas of practice, including failure to diagnose and treat myocardial infarction, coronary artery bypass graft surgery, percutaneous coronary intervention, and the use of tissue plasminogen activator. Empirical research on cardiology malpractice is presented, along with a sampling of up-to-date cases designed to illustrate common issues and impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Finally, myocardial IRI is a critical issue also for forensic pathologists since sudden death may occur despite timely reperfusion following AMI, that is one of the most frequently litigated areas of cardiology practice [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, myocardial IRI is a critical issue also for forensic pathologists since sudden death may occur despite timely reperfusion following AMI, that is one of the most frequently litigated areas of cardiology practice [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our study is not the first to ascertain that missed diagnoses of myocardial infarction are at the crux of much of cardiology malpractice litigation [19]. A 2017 retrospective analysis of malpractice claims involving myocardial infarction found that misdiagnosis was the most common claim.…”
Section: Discussionmentioning
confidence: 98%
“…When a medical malpractice suit is brought to court, the plaintiff has the burden of proving that the defendant breached his or her duty to provide patient care by departing from the current acceptable standards; thus, this study reflects, through case outcomes, the widely perceived and accepted standards of care within cardiothoracic surgery at present. One example lies in the perceived communication expectations between cardiothoracic surgeons and anesthesiologists or perfusionists during cases.…”
Section: Discussionmentioning
confidence: 99%
“…A number of cases related to cardiac surgical malpractice were likely not included, and selection biases may exist in terms of various aspects of case content, such as geographical location, plaintiff characteristics, or practice setting. However, although it could be anticipated that the attorney on the opposing end of the Jury's ruling in a case would be deincentivized to report it to a public database, the attorney on the victorious end would be equally as incentivized to use the verdict as a personal marketing tool, so the selection biases in each direction may ultimately cancel out one another.…”
Section: Discussionmentioning
confidence: 99%